PENGEMBANGAN STANDAR OPERASIONAL PROSEDUR (SOP) UNTUK PENGADAAN DAN PEMBAYARAN MATERIAL PADA PERUSAHAAN KONSTRUKSI PT XYZ - Paradisa Sukma; Ni Putu Ari Aryawati (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This study aims to create Standard Operating Procedures (SOP) forthe Procurement and Payment of Materials for PT XYZ, aconstruction services provider. The research method is qualitative anddescriptive, with data collected via interviews and observation.Interviews were conducted with the leadership (CEO) and employeesin five departments, namely: field (project), procurement(procurement), finance, cashier, and accounting. Then theobservation is done through direct observation. This researchproduced SOPs for material procurement and payment that weresuitable for PT XYZ.